The vegetative State : - Jennett, Bryan (Cambridge University Press, 2002)
The volume discusses the medical definition and criteria for diagnosis, its frequency and causes, and possible outcomes. The author also explores ethical arguments, including the conflict between sanctity of life and respect for the autonomy and best interests of the victim, and between killing and letting die. Legal issues are explored with details of landmark court cases from the U.S., Britain, and elsewhere. This well-informed and carefully constructed account will be a benchmark for medical specialists, ethicists, lawyers, and philosophers.